Integrating network pharmacology and experimental verification to decipher the immunomodulatory effect of Bu-Zhong-Yi-Qi-Tang against poly (I:C)-induced pulmonary inflammation - Hu, Liufang; Yamamoto, Marina; Chen, Jiali; Duan, Huifang; Du, Jing; He, Liangliang; Shi, Danfeng; Yao, Xinsheng; Nagai, Takayuki; Kiyohara, Hiroaki; Yao, Zhihong (Frontiers in Pharmacology, 2022)
Graphical Abstract